Alcances y desafíos del TCU “Cooperación interinstitucional para la difusión del francés a las comunidades” - Arias Corrales, Ileana (2013)
The following article presents the main scopes of the TCU 452 project in the period 2008-2010 in the areas of creation of educational materials, workshops for French teachers and workshops in French and/or French-speaking cultures for the public in general. Also, it outlines the challenges that will face the project in the years to come.